NUTRITION AS A FACTOR OF ADAPTATION TODDLERS TO CHILDREN'S EDUCATIONAL INSTITUTION - Дракина, Светлана Альбертовна; Перевощикова, Нина Константиновна (Mother and Baby in Kuzbass, 2017)
Nutrition is one of the most important factors from the moment of birth and participating in shaping the future of health. Complex physiological processes in the organism of the child is the second or third year of life requires a balanced daily intake of all major nutrients.Purpose: Analysis of actual power and possibilities of its correction in children attending the nursery children's educational institution.Materials and methods. The work was carried out in two stages. In the first phase of the mother for 14 days recorded the amount actually eaten by the children of servings for dinner on weekdays and full diet on Saturday and Sunday. At the same time for 10 days, we estimated the actual nutrition of children in preschool (in percent from the standard single servings). In the second phase of the study examined the possibility of correction of power.Results and their discussion. The analysis of the nutrition of children of nursery school and at home it was found that the product set meets the recommended and not limited by the consumption of vegetables, meat, fish, milk and sour-milk products. On the background of physiological correction of nutrition in children in the form of replacement of drinking cow's milk with a mixture of 3 rooms adapted for macro- and micronutrients for this age group, it was noted the positive dynamics of health status. Cropped signs of atopic dermatitis, functional disorders of the intestine, sleep problems, habit, improved appetite, reduced the number of acute respiratory diseases. Improved indicators of local immunity in natalem secret – the increase in lysozyme, secretory IgA. In nasutitermes recorded an increase in the columnar epithelium, a decrease in the number of eosinophils and neutrophils.Conclusion. Thus, the rational nutrition of children ensures improvement of local immunity and as a consequence of the increasing resistance of the child's body, as evidenced by the decrease in the number of SARS that facilitates easier period of adaptation to the children's educational institution.
Keywords: nutrition; early age; correction; children's educational institution